(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Immunological abnormalities are implicated in the pathogenesis of inflammatory diseases of the uveal tract. Investigation of the molecular mechanisms of various forms of endogenous uveitis from the standpoint of current immunology seems to be relevant from the theoretical and practical standpoints. This will provide a direction for further research on the development of pathogenetically grounded methods of treatment of uveitis. Purpose: to assess the expression levels of lymphocyte activation markers, intercellular adhesion marker (ICAM)-1 CD54, СD95 (FAS), and СD5, and neutrophil activation marker CD15, in the peripheral blood of patients with intermediate uveitis and healthy individuals. Material and Methods: Blood samples were taken from 14 patients (mean age, 34.0 ± 11.0 years) with intermediate uveitis before treatment and 26 practically healthy individuals (mean age, 36.0 ± 10.0 years). An immunohistocytochemical study using monoclonal antibodies was employed to assess the expression. Results: Expression of cell surface molecular markers on peripheral blood lymphocytes was significantly higher in patients with intermediate uveitis compared with controls. Mean percentage and absolute values of СD54 (ICAM-1) expression were 29.6 ± 3.5% and 674.18 ± 63.4 cell/µL, respectively, for patients, versus 14.2 ± 3.1% and 674.18 ± 63.4 cell/µL, respectively, for controls; CD95 (FAS), 28.5 ± 4.9% and 534.2 ± 59.5 cell/µL, for patients, versus 18.9 ± 3.1% and 254.18 ± 42.1 cell/µL, respectively, for controls; CD5, 23.4 ± 4.1% and 622.8 ± 53.5 cell/µL, respectively, for patients, versus 10.3 ± 1.96% and 152.11 ± 10.13 cell/µL, respectively, for controls. CD15, a neutrophil activation marker, was significantly (Mann-Whitney test, p < 0.05) higher expressed in patients (mean percentage expression, 28.7 ± 5.8%; mean absolute expression, 980.19 ± 58.4 cell/µL), than in controls (mean percentage expression, 14.2 ± 3.1%; mean absolute expression, 165.5 ± 32.1 cell/µL). Increased expression of lymphocyte activation markers may indicate a failure of autotolerance mechanisms as well as excessive immune response leading to intraocular inflammation. In addition, increased expression of СD 54 (ICAM-1) and СD 95 (FAS) may be a prognostic sign for increased inflammation in the eye. Conclusion: Immunological status of patients with intermediate uveitis is characterized by significantly increased expression of molecular markers such as intercellular adhesion marker (ICAM)-1 CD54, apoptosis marker СD95 (FAS), lymphocyte autoactivation marker СD5, and neutrophil activation marker CD15. Further research of longitudinal changes in these characteristics may be important for predicting the course of inflammation over time and determining the therapy needed.